Effects of Xiang Sha Yang Wei Wan on ethanol-induced gastric ulcer in sprague dawley rats: A histological study - Al-Qaraghuli , Ahmed S; Abdel Wahab, Emad M N; Al-Ani, Imad Matloub Dally; Faisal, Ghasak Ghazi (Faculty of Medicine, International Islamic University Malaysia, 2013)
Introduction: Xiang Sha Yang Wei Wan (XSYWW) is a Chinese traditional medicine that is used for gastrointestinal disorders, specifically gastric ulcer in many countries of South-East Asia. The aim of the study was to evaluate the potential effects of XSYWW on ethanol-induced gastric ulcer in rats by means of histological Study. On a similar basis of treatment, ranitidine, a conventional medication was used as gold standard. Methods: Fifty five male Sprague-Dawley rats (250-300 gm) were divided into four groups. Group I (ethanol treated group) was the control group and gastric ulcers were induced by administering 100% ethanol (1 ml/200 g). Group II (Pre-treatment group) was divided into two subgroups; they were orally fed with 1.0 gm/kg and 2.0 gm/kg respectively of XSYWW solution. Thirty minutes later they were administered with absolute ethanol as in group I. Group III, was given an oral dose of 2gm/kg of XSYWW solution after one hour of ethanol administration. Group IV was given an oral dose of 200mg/kg ranitidine solution after one hour of ethanol administration. Five rats from groups I, III and IV were sacrificed on day 1, 2 and 3 while the animals of group II were sacrificed one hour after ethanol administration. Results: Histological study of the stomachs from ethanol treated rats showed multiple ulcers of various depths that reached the muscularis and the serosa. Conclusion: Pre or post-treated rats with XSYWW showed that XSYWW has protective effect against ethanol-induced gastric mucosal lesion. However, there was a faster and more complete healing process in the ranitidine treated group when compared to the XSYWW treated subjects.